Incunabula from Canons’ Regular Libraries in the Wrocław University Library Collection - Kępa, Rafał (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
This paper attempts to determine the nature of incunabula collections, which used to belong to theCanons Regular monasteries in Wrocław and Żagań, and are now owned by the Wroclaw UniversityLibrary. Their analysis shows that both had similar character, quite typical for monastery libraries. Thelargest number of books are theological works. Among them, the most numerous are collections of sermonsand homilies (including such well-known authors as Jacobus de Voragine), followed by theologicaltreatises and liturgical books. Another group that should be mentioned are the philosophical writings,which include the works of such great authors as Saint Augustine, Boethius or Saint Thomas Aquinas.Some codices include legal texts, mostly in canon law. Silesian Canons Regular had also several medicalworks by various authors, including non-Christians, such as Averroes and Avenzohar. Somewhat surprisingis the presence of five books of Ovid, including a collection of his erotic poetry. This, however, seemsto confirm the eclectic nature of the collection characterizing most monastic libraries.As for the provenance of books, the overwhelming majority was produced by publishers from presentday Italy and Germany. It is no surprise that many of the texts of religious nature were printed in thecities of Italy, still less surprising is the close relationship of Silesian monasteries with the area of Germanculture.Notes of pedigree usually do not bring much information regarding the books’ history. Certainly,however, both collections deserve the attention of researchers.